2017
DOI: 10.1111/ajd.12540
|View full text |Cite
|
Sign up to set email alerts
|

Burden of human scabies in sub‐Saharan African prisons: Evidence from the west region of Cameroon

Abstract: Almost one-third of prisoners suffered from scabies in our prisons. A low educational level, the sharing of clothes/bedding and number of detainees/cell > 10 were independent determinants of the disease. Urgent measures must be undertaken to reduce the burden of scabies in our prisons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
3
14
0
2
Order By: Relevance
“…Similarly, in Northern Ethiopia (Tigray) [23], the risk of getting scabies was five times more in individuals having poor personal hygiene particularly poor hand washing practices. In contrast, different studies indicated that the prevalence of scabies was not influenced by personal hygiene [26, 27]. Experimental findings also showed that viability and number of Sarcoptes scabiei was not reduced by hand washing or rubbing hands with alcohol [28].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in Northern Ethiopia (Tigray) [23], the risk of getting scabies was five times more in individuals having poor personal hygiene particularly poor hand washing practices. In contrast, different studies indicated that the prevalence of scabies was not influenced by personal hygiene [26, 27]. Experimental findings also showed that viability and number of Sarcoptes scabiei was not reduced by hand washing or rubbing hands with alcohol [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although less common, contact with infested fomites including clothing, bedding and towels have been thought to play a role [5,7]. Outbreaks of scabies have occurred during wars, refugees/migration crisis [8] and in situations of overcrowding such as in schools [9][10][11], prisons and care homes [12]. Scabies has been reported to be associated with household size, low socioeconomic status and poor access to healthcare [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The figures observed here exceed the ones seen in the prison of Salto del Negro, in Gran Canaria, which have not been reported in the scientific literature 8 . Figures alarming as these have only been described in African prisons 26 . One of our current hypotheses is that there are one or more temporary residences that are infected, which are successively occupied by young marginalised homeless persons who are sexually promiscuous and do not have hygienic habits, who have ended up in prison for theft and drug dealing.…”
Section: Discussionmentioning
confidence: 99%
“…Se superan las cifras observadas en la prisión de Salto del Negro, en Gran Canaria, no reportadas en la prensa científica 8 . Cifras más alarmantes solo se han descrito en prisiones africanas 26 . Una de las hipótesis que contemplamos es la existencia de una o varias viviendas de tránsito infestadas, ocupadas sucesivamente por jóvenes marginales sin techo y sin hábitos higiénicos, con promiscuidad sexual, que acaban en prisión por delitos de robo y tráfico de drogas.…”
Section: Discussionunclassified